1979
DOI: 10.1017/s0003356100023096
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of different predictors of the lean content of pig carcasses 2. Predictors for use in population studies and experiments

Abstract: Linear measurements and sample joint dissections were examined as predictors of carcass lean percentage using data from 1060 carcasses comprising 108 subgroups (nine genotypes × two sexes × two feeding regimes × three slaughter weights). The potential predictors were examined in terms of precision, cost and the stability of their regression equations.Probed fat thickness 6·5 cm from the dorsal mid-line at the last rib (P2) was the individual measurement giving the most precise prediction (residual s.d. pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2

Year Published

1981
1981
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 8 publications
4
36
2
Order By: Relevance
“…https://doi.org/10.1079/PNS19860035 I 986 those based on White-bred populations. We have also found important differences in carcass lean content at equal fat thickness among pigs from different commercial breeding companies in Britain (Evans & Kempster, 1979) and have also suggested that relations can change significantly over time (Diestre & Kempster, 1985).…”
Section: Carcass Classification Schemesmentioning
confidence: 53%
See 1 more Smart Citation
“…https://doi.org/10.1079/PNS19860035 I 986 those based on White-bred populations. We have also found important differences in carcass lean content at equal fat thickness among pigs from different commercial breeding companies in Britain (Evans & Kempster, 1979) and have also suggested that relations can change significantly over time (Diestre & Kempster, 1985).…”
Section: Carcass Classification Schemesmentioning
confidence: 53%
“…Equations can be constructed separately for each treatment or individual treatment intercepts can be used together with pooled within-treatment dopes as in the double-sampling-with-regression procedure (Conniffe & Moran, 1972;Evans & Kempster, 1979). The double-sampling technique can be used effectively and anyone considering carcass-evaluation techniques is recommended to explore its use.…”
Section: Experiments and Population Studiesmentioning
confidence: 99%
“…On the other hand, the animal type bias found in the relationships between the reference method and the on-line instrumental methods (e.g. fat and muscle thickness measurements) seems to be a more serious problem (Branscheid, Komender, Oster, Sack, & Fewson, 1987;Engel, Buist, Font i Furnols, & Lambooij, 2004;Evans & Kempster, 1979;Gu et al, 1992;Planella & Cook, 1991;Wood & Robinson, 1989;Zelenák et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The biasing effect of population, sex and feeding regimen on the prediction of carcass lean concentration from P2 and carcass weight were previously identified by Evans and Kempster (1979). These authors, in disagreement with the present data, found the prediction from P2 to be stable in Subcutaneous fat 5-2 Sex 0-7 1-4 2-1 6-6 2-8 3-0 6-0 Feeding 0-1 0-2 0-5 0-1 1-8 0-9 2-7 Population and sex 3-6 5-1 5-7 8-9 5-9 5-9 8-2 slope over pig populations.…”
Section: Discussionmentioning
confidence: 99%